Insulin Sensitivity, Lipids, and Blood Pressure in Young American Blacks - Falkner, Bonita; Kushner, Harvey; Tulenko, Thomas; Sumner, Anne E.; Marsh, Julian B. (Arteriosclerosis, thrombosis, and vascular biology, 1995)
The purpose of this study was to determine whether insulin resistance was linked with alterations in plasma lipids in adult young blacks with borderline hypertension. Ninety-four American blacks participated (46 men, 48 women, age range 28 to 33 years). Within this group of 94 subjects, there were 60 normotensive (Nt) subjects and 36 subjects with borderline hypertension (BHt), defined as blood pressure > 135/85 mm Hg. None of the subjects were diabetic or receiving antihypertension medication. All participants had blood pressure and anthropometric measurements, a fasting lipid profile, an oral glucose tolerance test, and a euglycemic hyperinsulinemic clamp. Insulin-stimulated glucose utilization (M), determined by insulin clamp, was significantly lower in the BHt subjects compared with the Nt subjects (men, Nt 6.91 plus/minus 0.62 versus BHt 5.54 plus/minus 0.65; women, Nt 5.97 plus/minus 0.47 versus BHt 3.79 plus/minus 0.38 mg times kg sup -1 times min sup -1, P = .006). When M was corrected for adiposity and expressed in milligrams per kilogram of fat free mass (M'), the difference between Nt and BHt remained significant (P = .006). There was a significant correlation of M' with systolic blood pressure (r = -.393, P < .0001), HDL-C (r = .382, P < .0001), triglyceride level (r = -.308, P < .001), apolipoprotein A-I (r = .190, P = .033), and apolipoprotein B (r = -.277, P = .004). When all lipid variables were entered in a stepwise multiple linear regression analysis, HDL-C emerged as the most significant lipid component in the model for insulin resistance. These data suggest that in American blacks with mild hypertension, the risk for cardiovascular disease may be augmented in the presence of insulin resistance. (Arterioscler Thromb Vasc Biol. 1995;15:1798-1804.)